Changing Attitudes Toward House Arrest With Electronic Monitoring: The Impact of a Single Presentation? - Gainey, Randy R. (International journal of offender therapy and comparative criminology, 2003)
The notion that community support is critical for program success is a consistent theme in the literature on community-based corrections. Unfortunately, many citizens know very little about alternative sanctions, are misinformed about them, and do not view them favorably. At issue is whether information about alternative sanctions affects individuals' attitudes regarding them. To address this question, students in an upper division criminal justice course were surveyed before and after a presentation on electronic monitoring. Following the presentation, students were more likely to agree that electronic monitoring is punitive and that it meets several goals of the justice system. Implications for policy makers and educators are provided